2009
DOI: 10.1111/j.1464-5491.2009.02759.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparing hormonal and symptomatic responses to experimental hypoglycaemia in insulin‐ and sulphonylurea‐treated Type 2 diabetes

Abstract: Aims Patients with diabetes rely on symptoms to identify hypoglycaemia. Previous data suggest patients with Type 2 diabetes develop greater symptomatic and hormonal responses to hypoglycaemia at higher glucose concentrations than non-diabetic controls and these responses are lowered by insulin treatment. It is unclear if this is as a result of insulin therapy itself or improved glucose control. We compared physiological responses to hypoglycaemia in patients with Type 2 diabetes patients treated with sulphonyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…They approximate the upper and lower limits, respectively, of the non-diabetic glycaemic threshold for symptoms of insulin-induced hypoglycaemia [8][9][10]. The generic non-diabetic glycaemic threshold for impairment of cognitive function is <2.8 mmol/l [8][9][10], but higher glucose levels have been reported for some tests [11][12][13][14]. Glucose concentrations of both <3.0 mmol/l and <2.8 mmol/l cause defective glucose counterregulation and impaired awareness of hypoglycaemia, the core components of hypoglycaemia-associated autonomic failure in diabetes [5].…”
mentioning
confidence: 99%
“…They approximate the upper and lower limits, respectively, of the non-diabetic glycaemic threshold for symptoms of insulin-induced hypoglycaemia [8][9][10]. The generic non-diabetic glycaemic threshold for impairment of cognitive function is <2.8 mmol/l [8][9][10], but higher glucose levels have been reported for some tests [11][12][13][14]. Glucose concentrations of both <3.0 mmol/l and <2.8 mmol/l cause defective glucose counterregulation and impaired awareness of hypoglycaemia, the core components of hypoglycaemia-associated autonomic failure in diabetes [5].…”
mentioning
confidence: 99%
“…The counterregulatory hormone data in the present study, published in detail elsewhere, found no significant differences in counterregulatory hormone responses between the diabetes groups. 17 These findings are relevant to the increasing use of CGM in both research and clinical practice, particularly in type 2 diabetes. 15 Similar sensors and software are used in CGM systems such as the Medtronic Paradigm Ò , Abbott Navigator Ò , and Dexcom Ô (San Diego, CA) Seven Ò used therapeutically.…”
Section: Discussionmentioning
confidence: 94%
“…17 Baseline blood samples were taken before starting a primed infusion of Actrapid insulin made up in 0.9% NaCl containing 2 mL of autologous blood maintained at a rate of 1.5 U/kg/min. Glucose (20%) (Clintec Nutrition, Slough, UK) was infused through the same intravenous catheter at a variable rate to maintain BG at plateaus of 5.0, 4.0, 3.5, 3.0, and 2.5 mmol/L for 40 min each.…”
Section: Experimental Hypoglycemiamentioning
confidence: 99%
“…A recent study demonstrated that hormonal and symptomatic responses to hypoglycemia seem to be different for insulin and SUs. Interestingly, SU-treated subjects are more symptomatic of hypoglycemia at a higher glucose level than insulin-treated subjects [17]. This may protect them from severe hypoglycemia but hinder attainment of glycemic goals.…”
Section: Severe Hypoglycemia Cardiac Arrhythmia and Deathmentioning
confidence: 94%